Modelling runoff components and hydrological processes in glaciated catchments of the inner Tien-Shan, Kyrgyzstan - Sadyrov, Sanjar; Tanaka, Kenji; Satylkanov, Rysbek; Khujanazarov, Temur; Touge, Yoshiya; Fujita, Koji (Frontiers in Earth Science, 2024)
Accurately quantifying runoff sources and hydrological processes in glaciated mountain basins is crucial for water resource management under climate change. This study applied integrated land surface, glacier energy-mass balance and river routing models to determine the hydrological contributions from various runoff sources in glaciated basins within the inner Tien-Shan mountains of Kyrgyzstan. Gridded meteorological forcing data were downscaled to account for local topographic influences on solar radiation and cloud transmissivity processes. Model simulations are evaluated against observational discharge, glacier mass balance and snow water equivalent. Particularly for the Kara-Batkak Glacier reference site, shortwave radiation correction yielded in a more accurate simulations. The results revealed that the peak glacier melt contribution occurred in July and August, with some basins reaching up to 54%. On an annual basis, the average contribution from glaciers across the basins was found to be 19%, while the ratios of snowmelt and rainfall were 58% and 23%, respectively. This study demonstrated the utility of integrated modelling for understanding hydrological processes and quantifying runoff components under current climatic conditions in data-scarce high mountain regions. (Immerzeel et al., 2010;Chen et al., 2016), the effects of changing seasonality of flow and peak water availability may fuel domestic tensions economically, politically, and socially (Bernauer and Siegfried, 2012). However, to predict the future state of the ecosystem, it is critical to understand the processes taking place in mountainous areas and define runoff sources, including glacial runoff, which may be significantly reduced by the end of the century (